The use of aromatherapy in depression (Research, Society and Development, 2022)
Depressive disorders are characterized by a heterogeneity of symptoms, with suicidal thoughts being the most worrying. The treatment for depression basically consists of drug therapy, but about 4% of people who do this type of treatment do not show results and this demonstrates that alternative therapies can be the way to give these people back some dignity. Based on what has been exposed, the objective of this study was to search the literature for evidence that aromatherapy is an option for the treatment of depressive disorders, especially in patients unresponsive to conventional therapies. Therefore, a literature review was carried out in the PubMed database for articles that demonstrated the efficiency of aromatherapy. Aromatherapy has been used for thousands of years, but there are few studies that demonstrate its effectiveness for the treatment of depression and even these results are inconclusive, as most of them were just experiments performed on animals and those performed on humans were related with more transient depressions such as postpartum depression and menopausal depression. With this, it can be concluded that aromatherapy can become an alternative for the treatment of depression, given that its use comes from centuries, but more studies must be carried out on its effectiveness.